2013
DOI: 10.1111/anae.12321
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pre‐operative nerve stimulator‐guided femoral nerve block and fascia iliaca compartment block in patients with a femoral neck fracture

Abstract: SummaryWe undertook a randomised, controlled trial to compare the analgesic efficacy and opioid sparing effect of nerve stimulator-guided femoral nerve block with fascia iliaca compartment block in patients awaiting surgery for fractured neck of femur. Ten-centimetre visual analogue pain scores were measured before and 2 h after the block and opioid consumption was recorded in the 12-h period after the block. One hundred and ten patients were randomly assigned. Femoral nerve block provided superior pre-operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
75
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 12 publications
(11 reference statements)
0
75
1
2
Order By: Relevance
“…We feel that Newman et al's findings [1] should be accepted with three important caveats. First, the authors did not standardise to one nerve localisation technique (anatomical landmark or nerve stimulator or ultrasound) and therefore the degree to which the observed difference occurred because of differences in technique rather than nerve anatomy cannot be quantified.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…We feel that Newman et al's findings [1] should be accepted with three important caveats. First, the authors did not standardise to one nerve localisation technique (anatomical landmark or nerve stimulator or ultrasound) and therefore the degree to which the observed difference occurred because of differences in technique rather than nerve anatomy cannot be quantified.…”
mentioning
confidence: 83%
“…Regarding Newman et al's study [1], if 'the right amount' of local anaesthetic is injected into 'the right place' (the fascia iliaca compartment), it will spread to the femoral nerve and should produce an adequate femoral block, comparable with the femoral nerve block [2]. Larger volumes may allow spread to the other nerves in the compartment (obturator and lateral femoral cutaneous) or even the lumber plexus.…”
mentioning
confidence: 99%
“…We read with great interest the article by Newman et al [1]. The authors clearly have an excellent pain management team, and other hospitals should strive to provide early regional blockade as the authors have.…”
Section: S Whitementioning
confidence: 99%
“…I congratulate Newman et al for their well-conducted study that concluded that femoral nerve blockade significantly improved pre-operative analgesia compared with fascia iliaca blockade in patients with hip fracture [1].…”
mentioning
confidence: 99%
“…Newman et al [1] have identified that peripheral nerve stimulation to assist placement of local anaesthetic close to the femoral nerve and its branches gave superior results in their hands when compared with blind placement after perceived puncture of two fascial layers. Ultrasound-assisted methods are now gaining widespread adoption as these devices become more commonly available.…”
mentioning
confidence: 99%